Legal protection for parking services in the event of a motor vehicle loss - Zernis Cendramata Reessena; Padrisan Jamba (Jurnal Cakrawala Hukum, 2022)
Consumer protection is a business that contains principles, rules, or rules used to provide protection and protect consumer rights. Problems regarding the safety of vehicles parked in public places often occur. These problems include the loss of helmets, vehicle parts, and even frequent loss of parked cars. What is the responsibility of parking managers to consumers who use roadside parking services in Batam City if they experience a vehicle loss? Researchers carried out the data interview technique by interacting and communicating directly at the research location with the interviewees. For the loss of motorized vehicles using parking services, the responsibility lies with the parking operator, which organizes the parking service business that has obtained a permit from the Regional Government. If t the parking operator does not carry out the responsibility, then legal action can be taken, both litigation and non-litigation. As one of the essential elements in the transportation system, parking arrangements are necessary and a concern for local governments to create a sense of security and comfort in using public facilities.How to cite item:Â Reessena, Z., Jamba, P. (2022). Legal protection for parking services in the event of a motor vehicle loss.Â Jurnal Cakrawala Hukum, 13(2), 224-230. DOI:https://doi.org/10.26905/idjch.v13i2.7874.